2013
DOI: 10.1111/j.1477-2574.2012.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of outcomes in patients undergoing liver surgery in an enhanced recovery after surgery pathways

Abstract: This systematic review suggests that ERAS protocols can be successfully implemented in liver surgery. Length of stay is reduced without compromising morbidity, mortality or readmission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 31 publications
5
106
1
6
Order By: Relevance
“…Two systematic reviews showed a decrease in complications and/or a reduction of LoS without an increase of the readmission rate, corroborating the results of this present study [18,19]. A study by Dunne et al including hepatectomies for colorectal metastasis found that as ERAS experience increases with time, a progressive diminution of hospitalization time and critical care admission was noticed [30].…”
Section: Discussionsupporting
confidence: 90%
“…Two systematic reviews showed a decrease in complications and/or a reduction of LoS without an increase of the readmission rate, corroborating the results of this present study [18,19]. A study by Dunne et al including hepatectomies for colorectal metastasis found that as ERAS experience increases with time, a progressive diminution of hospitalization time and critical care admission was noticed [30].…”
Section: Discussionsupporting
confidence: 90%
“…In an effort to clarify the role of FT programs in liver resection, Coolsen and colleagues published a systematic review of two randomized controlled trials (RCTs), three case-control studies and one retrospective case series [14]. They demonstrated that FT programs reduced the length of hospital stay without compromising morbidity, mortality, or readmission rates in liver resection.…”
Section: Introductionmentioning
confidence: 99%
“…Published guidelines from the ERAS Society cover recommendations for perioperative care, not only for colorectal surgery [3,4] , but also pancreaticoduodenectomy [15] and radical cystectomy for bladder cancer [16] . In addition, enhanced recovery protocols have safely and successfully been implemented for other major elective abdominal procedures such as liver resections [17] , esophagectomy [18,19] , gastrectomy [20] , bariatric surgery [21] , hysterectomy [22] , and emergency surgery [23,24] .…”
Section: Surgical Disciplinesmentioning
confidence: 99%